National-Regional Component in the Training of Artists of Decorative-Applied Art - Vladimirovich Sokolov, Maxim; Stanislavovna Sokolova, Marina; Vladimirovna Shokorova, Larisa (International Journal of Engineering and Technology, 2018)
The article considers the regionalization of education as an important condition for preservation and development of ethnocultural artistic traditions. Regional culture is understood to mean a world of material and spiritual elements that make up being of particular region inhabitants with their constituent parts such as history, religion, folklore, and traditional applied art. The authors emphasize special role of culture and art universities in the process of humanizing art education. The article draws attention to the problem of identity in the modern global world and the importance of introducing the values of the past through the knowledge of the region’s cultural heritage to the modern person. In this context, the authors emphasize the importance of traditional folk art as an area of self-determination and human identity.The article proposes a set of special tasks for inoculation of a regional component in the educational process. The main methodological task is the formation of national historical self-awareness, group and individual self-identification, patriotism through the acquisition of cultural samples by their mastering in the process of creative activity and the further development of traditional arts and crafts in the new conditions of cultural existence.The article concludes the renewal of the content of teaching arts and crafts on the basis of its enrichment by studying various national cultures taking into account regional peculiarities becomes the most important thing at the present stage. The training of future artists of decorative and applied art should be based on the principles of cultural appropriateness, historicism, creative development and socialization, which presuppose students’ development in the process of nonmaterial culture learning